Electronic Payments, the Antidote of the Hidden Economy - Nitu, Alin Sergiu; Constantin, Aurelian (Acta Universitatis Danubius. Œconomica, 2022)
The hidden economy, known in everyday vocabulary as an undeclared, underground economy, etc., is a feature of today's world, with no global temporal and spatial limits, which has as its cause and purpose the avoidance of tax payments and / or the conduct of prohibited activities. Regardless of the forms in which it manifests itself, which are very diverse, complex and sometimes difficult to detect, it largely includes tax fraud, unregistered or partially registered work and criminal activities. Institutions interested in combating this phenomenon have adapted and intensified their activity to bring it to a controllable area so that in the end, as a long-term and difficult-to-achieve goal, it can be eradicated, if not completely, at least in a insignificant share compared to the real economy. As an equivalent of goods and services and a means of exchanging and procuring them, money, depending on the method of payment, creates the possibility for the actors involved to evade taxation, which why not recognize, in most cases is burdensome. It is proven that cash payments are favorable and conducive to the hidden economy, reducing or eliminating them by using electronic payments means a deep blow under the belt given to it, not only image, which can bring this type of economy in the controllable area as stated in beginning. This effort to generalize electronic payments has been somewhat helped by the international situation created by the Covid 19 pandemic, which in addition to serious problems has played an important role in raising awareness and awareness of the benefits of electronic payments and online commerce and implicitly taxing these transactions.